A method for preparing a fiber-reinforced investment casting shell
By pretreating the fibers and using them reasonably in the molded shell, the problems of complex fiber addition and insufficient strength of the molded shell in the prior art are solved, and the high humidity, high temperature strength and good breathability of the molded shell are achieved.
Patent Information
- Application Number
- CN202210970993.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-08-14
AI Technical Summary
In the prior art, when preparing investment precision cast molded shells, the fiber addition method is complex, which affects the uniformity and stability of the coating, and the wet and high-temperature strength of the molded shells are insufficient.
The fibers are etched and immersed with a mixed solution of butanone acetone and ionic solution to form activated pretreated fibers, and then these fibers are used in different levels of the mold shell and steam dewaxing and calcination are performed.
It significantly improves the wet strength and high temperature strength of the molded shell, enhances breathability, and is simple to operate without affecting the uniformity and stability of the paint.
Smart Images

Figure BDA0003796748360000061
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a fiber-reinforced investment mold precision casting shell, and belongs to the technical field of investment mold precision casting. Background Art
[0002] In investment casting production, the quality of the mold shell determines the quality of the casting. Generally, the mold shell is required to have sufficiently high wet strength to prevent the mold shell from cracking during transportation or dewaxing; higher high-temperature strength to prevent the mold shell from cracking during roasting and casting; and lower residual strength to make the casting easy to clean.
[0003] At present, the most advanced practice at home and abroad is to add inorganic and organic fibers into the coating. Fibers, as a common reinforcing material for composite materials, can effectively improve the mechanical properties of the matrix, and their application has become very common.
[0004] Patent application CN103639359A discloses a preparation method based on composite fiber reinforced investment casting shell, which uses ceramic and nylon composite fibers to reinforce the investment casting shell, which can not only enhance the shell strength and improve the shell air permeability, but also solve the problem of poor air permeability caused by increasing the shell thickness in order to ensure the strength of the shell prepared by the traditional process. However, its fiber adding method is more complicated, and inorganic fibers and organic fibers need to be added separately, and intermittent vibration of an ultrasonic device with an immersion probe is required to evenly disperse the fibers.
[0005] Patent application CN103962506A discloses a method for preparing a fiber-reinforced composite silica sol mold shell for investment casting. In order to solve the problem of low wet strength of the mold shell made by the prior art, organic fibers are added to the coating, but they are only added to the back layer coating and not introduced into the surface layer coating. It is estimated that the introduction of fibers into the surface layer coating will easily bring uniformity and stability problems and is not easy to introduce. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for preparing a fiber-reinforced investment casting shell, which is simple to operate and does not affect the uniformity and stability of the coating. To achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0007] A method for preparing a fiber-reinforced investment casting mold shell, comprising pre-treating the fiber to prepare a pre-treated fiber, and then using the pre-treated fiber to prepare a surface layer mold shell, a transition layer mold shell, and a back layer mold shell and perform slurry treatment, and finally performing steam dewaxing and roasting to obtain a pre-treated fiber;
[0008] The specific method of preprocessing is as follows:
[0009] (A) firstly etching the fiber with a mixture of butanone and acetone, taking it out and naturally drying it to obtain an etched fiber; in the mixture, the mass ratio of butanone to acetone is 3.5 to 5:1;
[0010] (B) Then the etched fiber is added to the ionic liquid for immersion until adsorption is saturated, taken out, and dried; the ionic liquid is an aqueous solution of calcium nitrate, yttrium nitrate or zirconium nitrate with a concentration of 2 mol / L.
[0011] Preferably, the fiber is selected from any one of polyethylene fiber, polypropylene fiber or polyamide fiber, and the fiber diameter is 20 to 30 μm and the fiber length is 10 to 15 mm.
[0012] Preferably, in step (A), the etching time is 10 to 30 minutes. The purpose of etching is to make the fiber form a porous structure, increase the specific surface area of the fiber, and provide an adsorption carrier for the subsequent chemical reaction.
[0013] Preferably, in step (B), the ionic liquid is adjusted according to the binder used to prepare the surface shell. When the binder is zirconium sol, the ionic liquid is an aqueous solution of calcium nitrate or yttrium nitrate; when the binder is yttrium sol, the ionic liquid is an aqueous solution of zirconium nitrate; when the binder is silica sol, the ionic liquid is an aqueous solution of calcium nitrate or yttrium nitrate.
[0014] Preferably, in step (B), the soaking time is 30 to 60 minutes.
[0015] Preferably, the preparation method of the surface shell is as follows:
[0016] Preparation of the first layer: adding refractory powder (yttrium oxide powder) to the binder at a powder-liquid ratio of 3.5-3.8, stirring evenly, then adding the pretreated fiber at a mass percentage of 5-8%, stirring to make it dispersed evenly, slowly and evenly adding the binder during the stirring process, so that the total powder-liquid ratio is reduced to 3.0-3.3, forming a first layer of slurry; then immersing the wax mold in the surface layer slurry for coating, controlling the material, sprinkling sand, and drying to obtain a first layer of shell;
[0017] Preparation of the second surface layer: continue to add adhesive to the remaining slurry of the first surface layer, adjust the powder-liquid ratio to 1.5-1.8, and form a second surface layer slurry; then immerse the wax mold into the second surface layer slurry for coating, controlling the material, sprinkling sand, and drying to obtain a second surface shell, which is the surface layer shell.
[0018] More preferably, the binder is zirconium sol, yttrium sol or silica sol.
[0019] More preferably, the adhesive is added for 10 to 30 minutes.
[0020] Preferably, the preparation method of the transition layer shell is as follows:
[0021] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 8-12s (coating 4 Cairn cups), then add the pretreated fiber at a mass percentage of 10-12%, stir to make it evenly dispersed, then immerse the surface layer shell into the transition layer coating for coating, control the material, sprinkle sand, and dry to obtain the transition layer shell; the sand is 30-60 mesh mullite sand; repeat this step, coat two layers of transition layers to obtain the transition layer shell.
[0022] Preferably, the preparation method of the back shell is as follows:
[0023] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 18-22s (coating 4 Caien cups), then add the pretreated fiber at a mass percentage of 12-15%, stir to make it evenly dispersed, then immerse the transition layer shell into the back layer coating for coating, control the material, sprinkle sand, and dry to obtain the back layer shell; the sand is 10-20 mesh mullite sand; repeat this step, coat three layers of back layers to obtain the back layer shell.
[0024] Preferably, the specific method of slurry treatment is as follows:
[0025] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 30-35s (coating 4 Caien cups), then add the pretreated fiber at a mass percentage of 12-15%, stir to make it evenly dispersed, then immerse the back layer shell into the slurry coating for coating and material control, and obtain the shell after drying.
[0026] Preferably, the process parameters of steam dewaxing are as follows: 150-170° C., steam pressure 0.4-0.6 MPa, and dewaxing time 9-15 minutes.
[0027] Preferably, the roasting process parameters are as follows: heating rate of 1-5°C / min, keeping at 340-380°C for 1-2 hours, keeping at 700-740°C for 1-2 hours, keeping at 1030-1070°C for 1-2 hours, cooling with the furnace, and then taking out of the furnace.
[0028] Beneficial effects of the present invention:
[0029] The present invention pre-treats the fiber to prepare the pre-treated fiber, and then uses the pre-treated fiber for the preparation of the surface shell, the transition shell, and the back shell, and the slurry treatment, and finally steam dewaxing and roasting are performed to obtain a fiber-reinforced investment casting shell. The present invention pre-treats the fiber in advance to increase its activity and specific surface area. After the activated fiber is added, it will not increase the viscosity of the system, but can also significantly improve the wet strength, high temperature strength, and air permeability of the shell.
[0030] This method is simple to operate and will not affect the uniformity and stability of the coating. The specific analysis is as follows:
[0031] 1. The pretreatment of the fiber is simple. The addition of activated fiber will not increase the viscosity of the system, but can also significantly improve the wet strength, high temperature strength and air permeability of the shell, and will not affect the uniformity and stability of the coating.
[0032] 2. The fiber can form a three-dimensional network structure in the investment casting shell, which improves the wet strength of the shell during dewaxing.
[0033] 3. The activated fiber has excellent adsorption capacity. It can adsorb ions in the ionic liquid during the activation process and metal ions in the adhesive in the coating. After the shell is roasted, the fiber is burned, forming micropores inside the shell, which improves the air permeability of the precision casting shell. At the same time, the ions adsorbed by the fiber can be used as high-temperature adhesives after the fiber is burned, and chemical reactions occur in the shell to form a three-dimensional network structure, which strengthens the high-temperature strength of the shell.
[0034] During high temperature sintering, the following reactions may occur inside the mold shell.
[0035] When the adhesive is zirconium sol, the ionic liquid is calcium nitrate and yttrium nitrate;
[0036] ZrO2+CaO→CaZrO3
[0037] ZrO2+Y2O3→Y2ZrO5
[0038] When the adhesive is yttrium sol, the ionic liquid is zirconium nitrate;
[0039] ZrO2+Y2O3→Y2ZrO5
[0040] When the adhesive is silica sol, the ionic liquid is calcium nitrate or yttrium nitrate.
[0041] SiO2+CaO→CaSiO3
[0042] SiO2+Y2O3→Y2SiO5
[0043] 4. In the preparation of pretreated fibers and the use of the pretreated fibers in the surface shell, transition shell, back shell and slurry coating, several key dosages are screened:
[0044] The mass ratio of butanone to acetone in the butanone-acetone mixture used in the pretreatment is 3.5 to 5:1. Within this ratio range, the specific surface area of the etched fiber is the largest, reaching 1500m 2 / g, greater or less than this ratio, the obtained fiber specific surface area is 800m 2 / g and 850m2 / g.
[0045] The etching time is 10 to 30 minutes. When it is within the proportional range, the specific surface area of the etched fiber is the largest, which can reach 1300 to 1500 m 2 / g, when it is less than 10min, the etching is not complete and the specific surface area is only 500-800m 2 / g, and the specific surface area will not continue to increase after 30min.
[0046] The immersion time in calcium nitrate solution is 30 to 60 minutes. Within the proportional range, the fiber ion adsorption rate after immersion is the highest, which can reach 99 to 99.9%. When it is less than 30 minutes, the adsorption is not complete, and the adsorption rate is only 50 to 60%. When it exceeds 60 minutes, the adsorption rate does not show a significant increase, and the value is 99.5%.
[0047] The mass percentage of the pretreated fiber in the surface layer shell, transition layer shell, back layer shell and when slurry is applied ranges of 5-8%, 10-12%, 12-15% and 12-15%, respectively. When the content is less than this range, the wet strength and high temperature strength of the shell will decrease. Under normal circumstances, they are 26MPa and 35MPa, respectively. When the content is less than this range, it will decrease to 18MPa and 25MPa. When the content is greater than this range, the viscosity of the system will increase and the stability of the slurry will decrease. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its contents.
[0049] The zirconium sol involved in the present invention was purchased from Qingdao Tianyao Industrial Co., Ltd.; the yttrium sol was purchased from Suzhou Youzi Nanomaterial Co., Ltd.; and the silica sol was purchased from Hubei Jinwei New Materials Co., Ltd.
[0050] Embodiment 1:
[0051] Step 1: Fiber pretreatment
[0052] A polyethylene fiber with a diameter of 20 μm and a length of 10 mm was immersed in a mixture of butanone and acetone (the mass ratio of butanone to acetone was 3.5:1) for etching. After etching for 10 minutes, the fiber was taken out and dried naturally.
[0053] The etched fiber was immersed in 2 mol / L calcium nitrate solution for 30 min and then taken out and dried after adsorption saturation.
[0054] Step 2: Prepare the surface shell
[0055] Preparation of the first layer: add yttrium oxide powder to the zirconium sol binder at a powder-liquid ratio of 3.5, stir evenly, then add 5% of the fiber prepared in step 1 at a mass percentage, stir to make it evenly dispersed, slowly add adhesive during the stirring process to reduce the total powder-liquid ratio to 3.3, and form a first layer of slurry; then immerse the wax mold in the surface layer slurry for coating, material control, sanding, and drying to obtain a first layer of shell.
[0056] Preparation of the second surface layer: continue to add adhesive to the remaining slurry of the first surface layer, adjust the powder-liquid ratio to 1.8, and form the second surface layer slurry; then immerse the wax mold into the second surface layer slurry for coating, material control, sanding, and drying to obtain the second surface shell.
[0057] Step 3: Prepare the transition layer shell
[0058] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 8s (coating 4 Caien cups), then add 10% of the fiber prepared in step 1 by mass, stir to make it evenly dispersed, then immerse the surface layer shell prepared in step 2 into the transition layer coating for coating, control the material, sprinkle sand, and dry to obtain the transition layer shell; the sand when sprinkling sand is 30-60 mesh mullite sand.
[0059] Repeat this step and apply two transition layers.
[0060] Step 4: Prepare the back shell
[0061] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 22s (coating 4 Cairn cups), then add 15% of the fiber prepared in step 1 at a mass percentage, stir to make it evenly dispersed, then immerse the transition layer shell prepared in step 3 into the back layer coating for coating, control the material, sprinkle sand, and dry to obtain the back layer shell; the sand when sprinkling sand is 10-20 mesh mullite sand.
[0062] Repeat this step to apply three layers of backing.
[0063] Step 5: Apply the paste
[0064] Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 35s (coating 4 Cairn cups), then add 15% of the fiber prepared in step 1 into it by mass percentage, stir to make it evenly dispersed, then immerse the back layer shell prepared in step 4 into the slurry coating for coating and material control, and obtain the shell after drying.
[0065] Step 6: Dewaxing and roasting
[0066] The shell obtained in step 5 is steam dewaxed and calcined.
[0067] Dewaxing process parameters: 170°C, steam pressure 0.6MPa, and dewaxing time controlled at 10min.
[0068] The roasting process parameters are as follows: the heating rate is 2°C / min, and the sintering system is 360°C for 2h; 720°C for 2h; 1050°C for 2h; then the furnace is cooled, taken out of the furnace, and the shell is obtained.
[0069] Embodiment 2:
[0070] The mass ratio of butanone to acetone in the butanone-acetone mixed solution used in the pretreatment was 5:1, and the etching time was 30 minutes; the immersion time in the calcium nitrate solution was 60 minutes.
[0071] The mass percentage ranges of the pretreated fibers in the surface layer shell, the transition layer shell, the back layer shell and when slurry is applied are 8%, 12%, 12% and 12% respectively.
[0072] The rest is the same as in Example 1.
[0073] Embodiment 3:
[0074] The mass ratio of butanone to acetone in the butanone-acetone mixed solution used in the pretreatment was 4:1, and the etching time was 20 minutes; the immersion time in the calcium nitrate solution was 40 minutes.
[0075] The mass percentage ranges of the pretreated fibers in the surface shell, transition shell, back shell and when slurry is applied are 7%, 11%, 13% and 13% respectively.
[0076] The rest is the same as in Example 1.
[0077] Comparative Example
[0078] The pretreated fibers were replaced with polyethylene fibers having a diameter of 20 μm and a length of 10 mm without any pretreatment, and the rest was the same as in Example 1.
[0079] Test example
[0080] The performance of the shell preparation methods of Examples 1 to 3 and the comparative example was investigated respectively, specifically including:
[0081] The fiber specific surface area was determined by BET surface area analysis;
[0082] The fiber ion adsorption rate is tested by the concentration difference method. First, the initial ion concentration of the solution is tested by the ICP method. After the adsorption is completed, the end point ion concentration is tested by the ICP method. The ion adsorption rate is calculated by the concentration difference between the two.
[0083] The viscosity of the top layer of slurry is tested using a 4# Caien cup.
[0084] The stability of the first layer of slurry is judged by whether the slurry sinks to the bottom or gels. For example, in the comparative example, the slurry sinks to the bottom and gels after 3 days.
[0085] The mold shell wet strength and high temperature strength are tested by three-point bending method and HB205352.1-2004 mold shell bending strength test.
[0086] Table 1. Performance test results
[0087]
[0088] As shown in Table 1, in Examples 1 to 3, the fiber has a large specific surface area, a high fiber ion adsorption rate, a suitable surface slurry viscosity, a high surface slurry stability, and the obtained mold shell has high wet strength and high temperature strength. The present invention pre-treats the fiber in advance to increase its activity and specific surface area. After the activated fiber is added, it will not increase the viscosity of the system, but also significantly improve the wet strength, high temperature strength and air permeability of the mold shell. The method is simple to operate and will not affect the uniformity and stability of the coating. The fiber in the comparative example is not pre-treated, which directly affects the wet strength and high temperature strength of the mold shell.
[0089] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing a fiber-reinforced investment casting shell, characterized in that: The fiber is pretreated to prepare pretreated fiber, and then the pretreated fiber is used for the preparation of the surface layer shell, the transition layer shell, the back layer shell and the slurry treatment, and finally steam dewaxing and roasting are performed to obtain; The specific method of preprocessing is as follows: (A) firstly etching the fiber with a mixture of butanone and acetone, taking it out and naturally drying it to obtain an etched fiber; in the mixture, the mass ratio of butanone to acetone is 3.5 to 5:1; (B) then adding the etched fiber into an ionic liquid for immersion until adsorption is saturated, taking it out, and drying it; the ionic liquid is an aqueous solution of calcium nitrate, yttrium nitrate or zirconium nitrate, with a concentration of 2 mol / L; The fiber is selected from any one of polyethylene fiber, polypropylene fiber or polyamide fiber, with a fiber diameter of 20 to 30 μm and a fiber length of 10 to 15 mm; In step (A), the etching time is 10 to 30 minutes; In step (B), the ionic liquid is adjusted according to the binder used to prepare the surface shell. When the binder is zirconium sol, the ionic liquid is an aqueous solution of calcium nitrate or yttrium nitrate; when the binder is yttrium sol, the ionic liquid is an aqueous solution of zirconium nitrate; when the binder is silica sol, the ionic liquid is an aqueous solution of calcium nitrate or yttrium nitrate; In step (B), the soaking time is 30 to 60 minutes.
2. The preparation method according to claim 1, characterized in that: The preparation method of the surface shell is as follows: Preparation of the first layer: add refractory powder to the binder at a powder-liquid ratio of 3.5-3.8, stir evenly, then add the pretreated fiber at a mass percentage of 5-8%, stir to make it dispersed evenly, slowly and evenly add the binder during the stirring process to reduce the total powder-liquid ratio to 3.0-3.3, forming a first layer of slurry; then immerse the wax mold in the surface layer slurry for coating, material control, sanding, and drying to obtain a first layer of shell; Preparation of the second surface layer: continue to add adhesive to the remaining slurry of the first surface layer, adjust the powder-liquid ratio to 1.5-1.8, and form a second surface layer slurry; then immerse the wax mold into the second surface layer slurry for coating, controlling the material, sprinkling sand, and drying to obtain a second surface shell, which is the surface layer shell.
3. The preparation method according to claim 1, characterized in that: The preparation method of the transition layer shell is as follows: Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 8-12s, then add the pretreated fiber at a mass percentage of 10-12%, stir to make it evenly dispersed, then immerse the surface layer shell into the transition layer coating for coating, control the material, sprinkle sand, and dry to obtain the transition layer shell; the sand is 30-60 mesh mullite sand; repeat this step, coat two layers of transition layers, and obtain the transition layer shell.
4. The preparation method according to claim 1, characterized in that: The preparation method of the back shell is as follows: Add 320 mesh mullite powder to the silica sol, adjust the coating viscosity to 18-22s, then add the pretreated fiber at a mass percentage of 12-15%, stir to make it evenly dispersed, then immerse the transition layer shell into the back layer coating for coating, control the material, sprinkle sand, and dry to obtain the back layer shell; the sand is 10-20 mesh mullite sand; repeat this step, coat three back layers to obtain the back layer shell.
5. The preparation method according to claim 1, characterized in that: The specific method of slurry treatment is as follows: Add 320 mesh mullite powder into silica sol, adjust the coating viscosity to 30-35s, add pretreated fiber at a mass percentage of 12-15%, stir to make it evenly dispersed, then immerse the back layer shell into the slurry coating for coating and material control, and obtain the shell after drying.
6. The preparation method according to claim 1, characterized in that: The process parameters of steam dewaxing are as follows: 150-170°C, steam pressure 0.4-0.6 MPa, dewaxing time 9-15 minutes; The roasting process parameters are as follows: heating rate is 1-5℃ / min, keeping at 340-380℃ for 1-2 hours, keeping at 700-740℃ for 1-2 hours, keeping at 1030-1070℃ for 1-2 hours, cooling with the furnace, and then taking out of the furnace.
Citation Information
Patent Citations
Preparation method of composite fiber enhanced fusible pattern precision casting shell
CN103639359A
Preparation method of fiber reinforced compound silica sol shell for investment casting
CN103962506A
Method for preparing fiber-reinforced thin-wall shell for casting titanium alloy smelting mold
CN102527937A
Zirconium oxide ceramic fiber prepared by adoption of viscose fiber and preparation method of zirconium oxide ceramic fiber
CN109440227A